Ochrobactrum intermedium septicemia - Pramodhini Subramanian; Namrata K Bhosale; Joshy M Easow; Chandni Chandramouli; K S Chenthil (Journal of Infection in Developing Countries)
Ochrobactrum species are emerging Gram-negative, non-fermenting bacteria with low virulence. Infection with the Ochrobactrum species is commonly nosocomial and has been reported in patients with indwelling medical devices and implants. Among the species of Ochrobactrum infecting humans, Ochrobactrum anthropic and Ochrobactrum intermedium are the commonest ones. We present a case of septicemia caused by Ochrobactrum intermedium in a 75-year-old patient with lower limb cellulitis. This report describes the epidemiology, clinical manifestations, laboratory diagnosis, antibiotic susceptibility pattern, and treatment of Ochrobactrum infections.